Antimicrobial and antibiofilm effects of essential fatty acids against clinically isolated vancomycin-resistant Enterococcus faecium - Wei, Ming; Wang, Peng; Li, Tianmeng; Wang, Qiangyi; Su, Mingze; Gu, Li; Wang, Shuai (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: Enterococcus faecium is a leading cause of hospital-acquired infections, which has become a serious public health concern. The increasing incidence of vancomycin-resistant E. faecium (VRE-fm) raises an urgent need to find new antimicrobial agents as a complement to traditional antibiotics. The study aimed to evaluate the antimicrobial and antibiofilm activity of essential fatty acids (EFAs) against VRE-fm, and further explore the molecular mechanism of the antibiofilm activity of EFAs.The microdilution broth method was used for antimicrobial susceptibility testing with traditional antibiotics and EFAs, including α-linolenic acid (ALA), eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), linoleic acid (LOA), γ-linolenic acid (GLA), and arachidonic acid (AA). The effect of EFAs on cell morphology of VRE-fm was investigated by scanning electron microscopy. The crystal violet method was used to evaluate the antibiofilm activities of EFAs against VRE-fm. Furthermore, the expression of biofilm-related genes (acm, atlA, esp, and sagA) of VRE-fm isolates under the action of GLA was analyzed using quantitative reverse transcription PCR (qRT-PCR) assay.Results: VRE-fm isolates were highly resistant to most traditional antibiotics, only highly susceptible to quinupristin-dalfopristin (90.0%), tigecycline (100%), and linezolid (100%). EPA, 2 DHA, and GLA exhibited excellent antimicrobial activity. The MIC50/90 of EPA, DHA, and GLA were 0.5/1, 0.25/0.5, and 0.5/1 mM, respectively. SEM imaging showed that strain V27 adsorbed a large number of DHA molecules. Furthermore, all EFAs exhibited excellent inhibition and eradication activities against VRE-fm biofilms. The biofilm inhibition rates of EFAs ranged from 45.3% to 58.0%, and eradication rates ranged from 54.1% to 63.4%, against 6 VRE-fm isolates with moderate biofilm formation ability. GLA exhibited remarkable antibiofilm activity against VRE-fm isolates. The qRT-PCR analysis showed that GLA could significantly down-regulate the expression of the atlA gene (P < 0.01) of VRE-fm.DHA showed the strongest antibacterial activity, while GLA showed the strongest antibiofilm effect among the EFAs with antibacterial activity. Our novel findings indicate that the antibiofilm activity of GLA may be through down-regulating the atlA gene expression in VRE-fm. Therefore, DHA and GLA had the potential to be developed as therapeutic agents to treat infections related to multiple antimicrobial-resistant E. faecium.